Factors that Influence the Reported Sensitivity of Rapid Antigen Testing for SARS-CoV-2 - Parvu, Valentin; Gary, Devin S.; Mann, Joseph; Lin, Yu-Chih; Mills, Dorsey; Cooper, Lauren; Andrews, Jeffrey C.; Manabe, Yukari C.; Pekosz, Andrew; Cooper, Charles K. (Frontiers in Microbiology, 2021)
Tests that detect the presence of SARS-CoV-2 antigen in clinical specimens from the upper respiratory tract can provide a rapid means of COVID-19 disease diagnosis and help identify individuals that may be infectious and should isolate to prevent SARS-CoV-2 transmission. This systematic review assesses the diagnostic accuracy of SARS-CoV-2 antigen detection in COVID-19 symptomatic and asymptomatic individuals compared to RT-qPCR, and summarizes antigen test sensitivity using meta-regression. In total, 83 studies were included that compared SARS-CoV-2 rapid antigen lateral flow testing (RALFT) to RT-qPCR for SARS-CoV-2. Generally, the quality of the evaluated studies was inconsistent, nevertheless, the overall sensitivity for RALFT was determined to be 75.0% (95% confidence interval [CI]: 71.0-78.0). Additionally, RALFT sensitivity was found to be higher for symptomatic versus asymptomatic individuals and was higher for a symptomatic population within 7 days from symptom onset (DSO) compared to a population with extended days of symptoms. Viral load was found to be the most important factor for determining SARS-CoV-2 antigen test sensitivity. Other design factors, such as specimen storage and anatomical collection type, also affect the performance of RAFLT. RALFT and RT-qPCR testing both achieve high sensitivity when compared to SARS-CoV-2 viral culture.